High Empathy of Early Childhood Grade B Children at Tunas Bangsa Kindergarten, Cipadung: Analysis of Supportive Learning Approaches - Rahman Agus Salim; Muhammad Ali; Asep Nurshobah (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2025)
Empathy is a crucial social skill that significantly influences the interpersonal development of early childhood. Defined as the ability to understand and share the feelings of others, empathy fosters prosocial behaviors such as helping, sharing, and cooperating. This study investigates the approaches employed by educators to cultivate empathy among young children in a preschool setting, specifically focusing on Class B at Taman Kanak-Kanak Tunas Bangsa Cipadung, Bandung. The research adopts a descriptive qualitative methodology, utilizing observation and interview techniques to gather data from teachers and students. Analysis was conducted through continuous data validation using triangulation to ensure reliability. Findings reveal that the preschool utilizes a constructivist approach to instill empathy, emphasizing active learning and social interactions among children. Key strategies include group work and habituation of prosocial behaviors, which facilitate the development of empathy through hands-on experiences. Observations indicated that children demonstrated cooperative behaviors, such as sharing toys and assisting peers in need, reflecting an early understanding of empathy. Additionally, the constructivist methods applied by teachers, rooted in the principles of Piaget and Vygotsky, align with the psychopedagogical foundations of the 2024 Merdeka Curriculum, which emphasizes student-centered learning and social-emotional competence.